Detection and identification of xerophilic fungi in Belgian chocolate confectionery factories. (April 2015) - De Clercq, Nikki; Van Coillie, Els; Van Pamel, Els; De Meulenaer, Bruno; Devlieghere, Frank; Vlaemynck, Geertrui
Abstract: Chocolate confectionery fillings are generally regarded as microbiologically stable. The stability of these fillings is largely due to the general practice of adding either alcohol or preservatives. Consumer demands are now stimulating producers to move away from adding alcohol or other preservatives to their confectionery fillings and instead to search for innovative formulations. Such changes in composition can influence the shelf life of the product and may lead to spoilage by xerophilic fungi. The aim of this study was to test whether the production environment of Belgian chocolate confectionery factories and common ingredients of chocolate confectioneries could be potential sources of contamination with xerophilic fungal species. In the factory environment, the general and strictly xerophilic fungal spore load was determined using an RCS Air Sampler device in combination with DG18 and MY50G medium, respectively. Four basic ingredients of chocolate confectionery fillings were also examined for fungal spore levels using a direct plating technique. Detected fungi were identified to species level by a combination of morphological characterization and sequence analysis. Results indicated a general fungal spore load in the range of 50–250 colony forming units per cubic meter of air (CFU/m 3 air) and a more strict xerophilic spore load below 50 CFU/m 3 air. These results indicate rather low levels of fungal spores present in the factory environment. The most prevalent fungi in the factory environment were identified as Penicillium spp., particularly Penicillium brevicompactum . Examination of the basic ingredients of confectionery fillings revealed nuts to be the most likely potential source of direct contamination. In nuts, the most prevalent fungal species identified were Eurotium, particularly Eurotium repens . Highlights: Low levels of fungal spores were recovered from the factory environment. Both general and xerophilic fungal species were recovered from the factory air. The most frequently contaminated nuts can be an important source of contamination. Penicillium sp. was the most prevalent genus in the factory environment. Nuts were shown to be mostly contaminated by Eurotium sp.